P6 The use of 5-ALA fluorescence in excision of supratentorial endodermal cyst. Issue 3 (14th February 2019) - Raslan, A; Acharya, S; Lavrador, JP; Vergani, F; Bhangoo, R; Ashkan, K
Abstract : Objectives: The first documented use of 5-ALA in the excision of an intraparenchymal endodermal cyst. Design: Case review. Subjects: 52 year old female presented with headaches, progressive right sided hemiparesis and anomic aphasia. She had a large cystic frontal lesion, adjacent of the frontal horn of the lateral ventricles cyst which did not show any nodular or solid component, and did not enhance with gadolinium. Methods: Case report and review of the literature. Results: 5-ALA assisted, image guided fenestration of the cystic lesion and insertion of a ventricular catheter connected to an Ommaya reservoir was performed. The cyst wall was observed under the microscope and it fluoresced with 5-ALA. Multiple biopsies were obtained from this tissue, which confirmed diagnosis of endodermal cyst. The patient had improvement in clinical symptoms and size of the cyst radiologically in both the immediate post-operative period and the 6 months follow up. Conclusions: Previous reports described the use of 5-ALA to identify tumour cells within the solid component of cystic haemangioblastomas as well as in cystic ependymomas where the cystic component does not fluoresce. In our patient, the homogeneous fluorescence of the wall suggested that this was indeed a different entity from a haemangioblastoma or an ependymoma because of the different pattern of fluorescence observed. 5-ALA-assisted resection of cystic lesions should be considered when a tumoral origin is uncertain.